Yield improvement in maize for tolerance to low soil nitrogen - Ajala, S.; Olaniyan, A.B.; Olayiwola, M.O.; Job, A.O. (Wiley, 2018)
Low soil nitrogen limits maize (Zea mays L.) production in the West and Central African subregion. Levels of residual genetic variability were determined in two low‐N populations using selfed progeny evaluations, and results obtained indicate large genotypic and phenotypic variances for grain yield under both low‐ and high‐N environments for effective selection, while heritability estimates were generally low. Ear aspect and stay green were the most important traits contributing to grain yield for both populations. Selection reduced days to flowering, ASI and ear aspect, but increased plant height and yield. Yield gains of more than 25% occurred for the two populations under both low and high N with the most significant change of 42% occurring in one population under high N.